Efficacy and safety of telitacicept combined with immunosuppressive therapy for IgA nephropathy: a retrospective multicenter cohort study - Zeng, Fang; Yang, Yang; Tan, Fei; Li, Yebei; Ren, Daijin; Cai, Chengmin; Wang, Jiang; Yan, Wenjun; Xie, Xiaojie; Wang, Yu; Yi, Lu; Xu, Shizhang; et al. (Frontiers in Immunology, 2026)
BackgroundTo investigate the efficacy and safety of telitacicept combined with glucocorticoid/mycophenolate mofetil (GM) versus telitacicept in the treatment of immunoglobulin A nephropathy (IgAN).MethodsThis retrospective, multicenter cohort study enrolled patients aged ≥ 18 years with biopsy-proven IgAN who were treated with telitacicept. All participants had a baseline eGFR ≥ 30 mL/min/1.73 m² and proteinuria excretion ≥ 0.75 g/day after receiving at least 1 month of optimized supportive treatment. Clinical data were collected over 9 months.ResultsA total of 256 patients were enrolled in the study, with 125 patients receiving telitacicept monotherapy and 131 patients receiving telitacicept plus GM therapy. The mean age was 39.5 ± 11.6 years, and 100 patients (39.1%) were male. At 9 months, the telitacicept + GM group showed a significantly greater reduction in proteinuria (-1.32 g/day versus -0.94 g/day, P < 0.001) and exhibited better eGFR slope (2.74 mL/min/1.73 m2/year versus -0.56 mL/min/1.73 m2/year, P = 0.014) compared to the telitacicept group. Similar reductions in urinary red blood cell count were observed in both groups, but the telitacicept + GM group exhibited a significantly greater median change at 9 months (-35.5/µL versus -9.0/µL, P = 0.009). Kaplan-Meier analysis revealed a significant benefit for the telitacicept + GM group over telitacicept monotherapy in both complete (54.2% vs. 40.8%, P = 0.005) and overall (78.6% vs. 70.4%, P = 0.014) remission rates. After adjusting for various factors, multivariable Cox regression analysis indicated a significantly higher likelihood of complete [adjusted HR 2.18 (95% CI 1.46-3.22), P < 0.001] and overall [adjusted HR 1.46 (95% CI 1.08-2.00), P = 0.013] remissions in the telitacicept + GM group at 9 months. Benefits were consistent across subgroups, with no significant interaction effects. Although the telitacicept + GM group was associated with a higher overall incidence of adverse events (28.2% versus 11.2%), no serious adverse events were reported in either group.ConclusionTelitacicept + GM regimen significantly reduced proteinuria and hematuria, maintained stable renal function in patients with IgAN, with no serious adverse events occurring.